Building Information Modeling (BIM) Use in Turkish Construction Industry - Aladag, Hande; Demirdogen, Gokhan; Isik, Zeynep (ELSEVIER SCIENCE BV, 2016)
Changing of business conditions due to globalization, improved technology, transformed demands, needs of customers and etc. gives a rise to increase a competition in construction industry. In this context, in order to survive and sustain in the long term, construction companies should progress in the field of technology and innovation. Thus, innovation approaches such as information technology (IT) used in construction is one of the most essential in terms of competitiveness for the construction industry's success. Among IT tools such as designing and structural analyses programs (CAD, Revit, SAP2000), enterprise resource planning (ERP) and data management programs; the BIM technologies became a major shift for the construction industry in order to organize the reciprocal interdependencies between different stakeholders considering the increasing complexity of construction projects in design, bidding, construction and maintenance processes also with additional benefits on change control, decrease in repetition, energy efficiency, health and safety, risk and quality management. Taken into consideration of the worldwide rising importance of the BIM technologies, Turkish construction companies should tend towards the BIM use in order to increase their global competitiveness and to provide the sustainability of Turkish construction industry's performance. In this context, the main aim of this study is to diagnose Turkish construction industry to develop a clear understanding of the BIM adoption, to investigate challenges and benefits of the BIM applications in Turkish construction companies and to provide recommendations for the Turkish construction industry about the BIM implementation. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Information technology (IT) use; building information modelling (BIM); construction industry; focus group discussion; simple multi attribute rating technique (SMART); Construction & Building Technology; Engineering